NAction! How Can Neuraminidase-Based Immunity Contribute to Better Influenza Virus Vaccines? - Krammer, Florian; Fouchier, Ron A. M.; Eichelberger, Maryna C.; Webby, Richard J.; Shaw-Saliba, Kathryn; Wan, Hongquan; Wilson, Patrick C.; Compans, Richard W.; Skountzou, Ioanna; Monto, Arnold S. (mBio, 2018)
Neuraminidase is one of the two surface glycoproteins of influenza A and B viruses. It has enzymatic activity that cleaves terminal sialic acid from glycans, and that activity is essential at several points in the virus life cycle. While neuraminidase is a major target for influenza antivirals, it is largely ignored in vaccine development. Current inactivated influenza virus vaccines might contain neuraminidase, but the antigen quantity and quality are varied and not standardized. While there are data that show a protective role of anti-neuraminidase immunity, many questions remain unanswered. These questions, among others, concern the targeted epitopes or antigenic sites, the potential for antigenic drift, and, connected to that, the breadth of protection, differences in induction of immune responses by vaccination versus infection, mechanisms of protection, the role of mucosal antineuraminidase antibodies, stability, and the immunogenicity of neuraminidase in vaccine formulations. Reagents for analysis of neuraminidase-based immunity are scarce, and assays are not widely used for clinical studies evaluating vaccines. However, efforts to better understand neuraminidase-based immunity have been made recently. A neuraminidase focus group, NAction!, was formed at a Centers of Excellence for Influenza Research and Surveillance meeting at the National Institutes of Health in Bethesda, MD, to promote research that helps to understand neuraminidase-based immunity and how it can contribute to the design of better and broadly protective influenza virus vaccines. Here, we review open questions and knowledge gaps that have been identified by this group and discuss how the gaps can be addressed, with the ultimate goal of designing better influenza virus vaccines.